MYC Association with Cancer Risk and a New Model of MYC-Mediated Repression - Cole, M. D. (Cold Spring Harbor perspectives in medicine, 2014)
MYC is one of the most frequently mutated and overexpressed genes in human cancer but the regulation of MYC expression and the ability of MYC protein to repress cellular genes (including itself) have remained mysterious. Recent genome-wide association studies show that many genetic polymorphisms associated with disease risk map to distal regulatory elements that regulate the MYC promoter through large chromatin loops. Cancer risk-associated single-nucleotide polymorphisms (SNPs) contain more potent enhancer activity, promoting higher MYC levels and a greater risk of disease. The MYC promoter is also subject to complex regulatory circuits and limits its own expression by a feedback loop. A model for MYC autoregulation is discussed which involves a signaling pathway between the PTEN (phosphatase and tensin homolog) tumor suppressor and repressive histone modifications laid down by the EZH2 methyltransferase.